Farm level survey of spore‐forming bacteria on four dairy farms in the Waikato region of New Zealand. Issue 4 (3rd March 2017) - Gupta, Tanushree B.; Brightwell, Gale
Abstract: The aim of our study was to determine the occurrence and diversity of economically important spore‐forming bacteria in New Zealand dairy farm systems. Farm dairy effluent (FDE) collected from Waikato dairy farms were tested for the presence of spore‐forming bacteria, using a new culture‐based methodology followed by genomic analysis. An enrichment step in which samples were inoculated in cooked meat glucose starch broth under anaerobic conditions, aided in the differential isolation of Bacillus and Clostridium species. Furthermore, the use of molecular methods such as ERIC genotyping, 16S rRNA gene sequence analysis identified different spore‐forming bacteria present in FDE. C. sporogenes signature PCR gave further information on the phylogenetic relationship of the different Clostridium spp. isolated in this study. In total 19 Bacillus spp., 5 Paenibacillus spp. and 17 Clostridium spp. were isolated from farm dairy effluent. Sequence types similar to economically important food spoilage bacteria viz: C. butyricum, C. sporogenes and members of the Paenibacillus Genus were isolated from all four farms, whereas, sequence types similar to potential toxigenic, B. cereus, C. perfringens, C. butyricum, and C. botulinum were found on at least three of the farms. Sampling of farm dairy effluent provides a good indicator of farm level prevalence of bacterial load as it is used to irrigate dairy pasture in New Zealand. This study highlights the presence of various spore‐forming bacteria in dairy waste water and indicates the implementation of good hygienic farm practices and dairy waste effluent management. Abstract : Use of a new cultural methodology has assisted in identifying spore‐forming bacteria from environmental samples, which further helped us investigating the diversity of spore‐forming bacteria in our dairy farms.